Influencing factors of destination choice of ski tourism enthusiasts: A means-end chain analytical perspective - Sun, Hui; Xie, Xia; Gao, Jun; Zhang, Lei (Frontiers in Psychology, 2022)
Drawing on a means-end chain analytical perspective, this study explores the main factors affecting the destination choice of ski tourism enthusiasts. Three levels of main factors, including destination attribute, experience consequence, and personal value, were first explored via a soft laddering interview (N=28), followed by a questionnaire survey (N=339). The results show that ski resort's condition is the most important destination attribute to ski tourism enthusiasts, with the strongest impact on their experience consequence. In addition to the value needs of positive emotion and self-adjustment, ski tourism enthusiasts also show a strong need for self-development.